In utero betamethasone affects 3β-hydroxysteroid dehydrogenase and inhibin-α immunoexpression during testis development. (29th March 2016) - Pedrana, G.; Viotti, H.; Lombide, P.; Sanguinetti, G.; Pino, C.; Cavestany, D.; Sloboda, D. M.; Martin, G. B.
Abstract : Prenatal glucocorticoids, commonly used in women at risk of preterm delivery, can predispose the newborn to disease in later life. Since male reproductive function is likely to reflect testis development during fetal life, we studied the effects of prenatal glucocorticoids on two key intra-testicular factors that play roles in cellular proliferation and differentiation, 3β-hydroxysteroid dehydrogenase (3β-HSD) and inhibin-α. Pregnant sheep ( n =42) were treated with betamethasone (0.5 mg/kg) or saline (control) at 104, 111 and 118 days of gestation (DG). Testicular tissue was sampled from fetuses at 121 and 132DG, and from lambs at 45 and 90 postnatal days (PD). Within the betamethasone treated group, 3β-HSD immunostaining area was greater at 121DG than at 90PD ( P =0.04), but the intensity of immunostaining was higher at 90PD than at 121DG ( P =0.04), 132DG ( P =0.04) and 45PD ( P =0.03). Control animals showed no changes in 3β-HSD area or intensity of immunostaining. No significant differences were observed between treated and control animals in immunostaining area, but immunostaining was more intense in the treated group than in the control group at 90PD ( P =0.03). For inhibin-α, the proportion of immunostaining area declined in treated offspring from 121DG to 45PD, in contrast to control values, but recovered fully by 90PD, concomitantly with the onset of spermatogenesis. In conclusion, prenatal betamethasone increased the postnatal testicular expression of inhibin-α but reduced the expression of 3β-HSD. These effects could compromise androgen-mediated testicular development and therefore adult capacity for spermatogenesis.